POLITIK UANG DALAM KERANGKA DEMOKRASI DAN PROBLEMATIKA PENEGAKAN HUKUMNYA - Budi Heryanto (Jurnal Hukum Mimbar Justitia, 2023)
The practice of Politics Money is a violation in the administration of elections. In these elections not only for the president and vice presidential elections but also for members of the legislature at all levels. The practice of money politics also often occurs, especially in the area of Sukabumi Regency. The identification of this problem is to find out the background of money politics criminal acts in the 2019 Legislative Election in Sukabumi District, Enforcement of Money Political Crimes in the 2019 Legislative Election by the Sukabumi Regency Election Supervisory Board and the Gakkumdu Center Authority in Handling Money Political Crimes in 2019 Legislative Election in 2019 in Sukabumi Regency Law Number 7 of 2017 Regarding General Elections. The method used in research is normative jurisdiction that is to find and examine the laws and regulations that are relevant to research and also derived from library materials. Keywords: Money Politics; Bawaslu; Sentra Gakkumdu.